2009
DOI: 10.1073/pnas.0902358106
|View full text |Cite
|
Sign up to set email alerts
|

Programmed loss of millions of base pairs from a vertebrate genome

Abstract: In general, the strict preservation of broad-scale structure is thought to be critical for maintaining the precisely tuned functionality of vertebrate genomes, although nearly all vertebrate species undergo a small number of programmed local rearrangements during development (e.g., remodeling of adaptive immune receptor loci). However, a limited number of metazoan species undergo much more extensive reorganizations as a normal feature of their development. Here, we show that the sea lamprey (Petromyzon marinus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
197
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(206 citation statements)
references
References 29 publications
8
197
0
1
Order By: Relevance
“…KF318001-KF318013). Because it is known that ∼20% of germ-line DNA is lost in the somatic tissues of lamprey resulting from a developmentally programmed genome rearrangement (19), the blood library was used only to ensure complete coverage of the lamprey Hox gene repertoire. A combination of ab initio and homology-based methods was used to predict genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KF318001-KF318013). Because it is known that ∼20% of germ-line DNA is lost in the somatic tissues of lamprey resulting from a developmentally programmed genome rearrangement (19), the blood library was used only to ensure complete coverage of the lamprey Hox gene repertoire. A combination of ab initio and homology-based methods was used to predict genes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these CNEs may represent part of the core set of cis-regulatory elements that were present in the common ancestor of vertebrates. genome of the sea lamprey has revealed the presence of two Hox clusters and eight other Hox genes that could not be assigned to any cluster (19). Interestingly, previous phylogenetic analysis of sea lamprey Hox genes had suggested that the Hox clusters of sea lamprey and gnathostomes arose from independent duplications and that the last common ancestor of cyclostomes and gnathostomes had a single Hox cluster (20).…”
mentioning
confidence: 99%
“…The difference in the number of tenascin genes identified in the 2 species may be due to the fact that the genome of P. marinus was sequenced from DNA taken from adult liver prior to the remarkable finding that hundreds of millions of base pairs are deleted from somatic cell lineages during the course of lamprey embryogenesis. 39 Germ cells were used as a source of DNA for the genomic sequencing of Lethenteron japonicum, which may account for the presence of the second tenascin. Although initial studies concluded that the agnathan/gnathostome divergence occurred after the 2 rounds of genome duplication early in vertebrate evolution, 28,40 recent study of Hox genes in the Japanese lamprey has led to the suggestion that genome duplications may have occurred independently in the lamprey lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Neither the 2012 assembly for the sea lamprey (Smith et al 2013) nor the 2013 assembly for the Japanese lamprey (Mehta et al 2013) fully meet the criterion, however. It should be emphasized that the missing data from the 2012 sea lamprey assembly are not because of programmed loss of DNA during development (Smith et al 2009). The main reason for the deficiency is because a large number of trace reads were omitted during the assembly process, mostly because of being considered repetitive DNA.…”
Section: Discussionmentioning
confidence: 99%